Acurácia e prevalência das características definidoras do diagnóstico Troca de gases prejudicada em crianças - Alan Alves de Oliveira Araújo; Lívia Maia Pascoal; Paula Vitória Costa Gontijo; Marcos Venícios de Oliveira Lopes; Marcelino Santos; Simony Fabíola Lopes Nunes (Universidade Federal do Ceará, 2019)
Objective to evaluate the accuracy and to determine the prevalence of the defining characteristics of the nursing diagnosis Impaired gas exchange in children with respiratory diseases.Methods cross-sectional study carried out with 236 children who were in the initial 48 hours of hospital admission. A questionnaire was used with sociodemographic data and physical examination of the respiratory system to identify the defining characteristics of the studied diagnosis. For the analysis of the accuracy, the sensitivity and specificity measures were calculated.Results the diagnosis Impaired gas exchange was present in 21.6% of the sample and the most prevalent defining characteristics were dyspnea and tachycardia. Regarding the accuracy measures, the characteristics that presented high sensitivity values were dyspnea and abnormal respiratory pattern, while cyanosis, hypoxemia, and restlessness obtained high values of specificity.Conclusion the characteristics that stood out both for the accuracy measures and for the prevalence were dyspnea and abnormal respiratory pattern.